A phylogenetically distinctive and extremely heat stable light-driven proton pump from the eubacterium Rubrobacter xylanophilus DSM 9941(T) - Kanehara, Kanae (Sci Rep, 2017)
Rhodopsins are proteins that contain seven transmembrane domains with a chromophore retinal and that function as photoreceptors for light-energy conversion and light-signal transduction in a wide variety of organisms. Here we characterized a phylogenetically distinctive new rhodopsin from the thermophilic eubacterium Rubrobacter xylanophilus DSM 9941(T) that was isolated from thermally polluted water. Although R. xylanophilus rhodopsin (RxR) is from Actinobacteria, it is located between eukaryotic and archaeal rhodopsins in the phylogenetic tree. Escherichia coli cells expressing RxR showed a light-induced decrease in environmental pH and inhibition by a protonophore, indicating that it works as a light-driven outward proton pump. We characterized purified RxR spectroscopically, and showed that it has an absorption maximum at 541 nm and binds nearly 100% all-trans retinal. The pK(a) values for the protonated retinal Schiff base and its counterion were estimated to be 10.7 and 1.3, respectively. Time-resolved flash-photolysis experiments revealed the formation of a red-shifted intermediate. Of note, RxR showed an extremely high thermal stability in comparison with other proton pumping rhodopsins such as thermophilic rhodopsin TR (by 16-times) and bacteriorhodopsin from Halobacterium salinarum (HsBR, by 4-times).